SISTEM PENGUKURAN DETAK JANTUNG MANUSIA MENGGUNAKAN MEDIA ONLINE DENGAN JARINGAN WI-FI BERBASIS PC - AHMAD NAWAWI HARAHAP (Saintia Fisika, 2013)
Heart is a vital organ inside human body. Its function is for blood circulationinside body through vein. Heart Beat frequency and strength are different from personto person. Heart rate detection is needed to determine whether or not a heart condition..Usually, the detection of heart beat is conducted by touching fein beat at human hand.The method needs a high consentration and needs a stopwatch. Modern technologyallows us to produce automatic instruments to do heart beat monitoring through fein.The instrument built will detect heart beat through blood flow frequency at hand finger,and will process the information electronically. This instrument will show the totalheart beat in every minute and the beat rhythm in graphic visualitation using GraphicPC, so that the result can be viewed on the monitor screen.Keywords : Heart Beat, Blood Flow, PC